2018
DOI: 10.3389/fpsyg.2018.01444
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone Restriction and Its Effect on Subjective Withdrawal Related Scores

Abstract: Excessive smartphone use has been associated with a number of negative consequences for the individual and the environment. Some similarities can be observed between excessive smartphone usage and several behavioural addictions, and continual usage constitutes one of several characteristics included in addiction. In the extreme high end of the distribution of smartphone usage, smartphone restriction might be expected to elicit negative effects for individuals. These negative effects may be regarded as withdraw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
58
3
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(70 citation statements)
references
References 54 publications
7
58
3
2
Order By: Relevance
“…When respondents cannot use their smartphone, they experience negative feelings, leading to withdrawal symptoms and fear of missing out (Eide et al 2018;Stieger and Lewetz 2018). In the present study, 20-34-year-olds reported this component the most, but the results also showed that withdrawal occurred among the 35-50 and 50+ age groups.…”
Section: Discussioncontrasting
confidence: 50%
“…When respondents cannot use their smartphone, they experience negative feelings, leading to withdrawal symptoms and fear of missing out (Eide et al 2018;Stieger and Lewetz 2018). In the present study, 20-34-year-olds reported this component the most, but the results also showed that withdrawal occurred among the 35-50 and 50+ age groups.…”
Section: Discussioncontrasting
confidence: 50%
“…The corollary to smartphone restriction -constant smartphone use -is associated with higher levels of negative affect (Horwood and Anglim, 2019). Studies on short breaks from smartphone use is limited, and the potential anxiety-provoking experiences related to "fear of missing out" (FOMO) from social media has largely been studied during longer periods of restriction than 6 min (Eide et al, 2018;Stieger and Lewetz, 2018). Investigations on the mood effects from short-term smartphone restriction is needed to investigate this potential explanation.…”
Section: Discussionmentioning
confidence: 99%
“…Fear of missing out describes people's fear of detachment and the desire to stay continually connected with what others are doing (Kang et al, 2019). It is usually regarded as a personality trait that leads to self-initiated behavior, and may cause individuals to neglect activities that are more compatible with their interests, goals, and values (Eide et al, 2018). In consumer behavior, FoMO is viewed as a social phenomenon that leaves people feeling alienated from their current experiences (Kang et al, 2019).…”
Section: The Role Of Fomomentioning
confidence: 99%
“…As members of society, consumers have connections with family, schoolmates, colleagues, neighbors, and social groups in their daily lives. Individuals with a high level of FoMO tend to be more aware of what others are doing, and seek to meet their needs in order to connect with others (Eide et al, 2018). The expectation of praise from others may reflect an individual's need to seek novelty.…”
Section: The Mediating Role Of Fomo Between Psychological Needs and Bmentioning
confidence: 99%